Effect of arm movement and task difficulty level on balance performance in healthy children: are there sex differences? - Thomas Muehlbauer; Mathew W. Hill; Simon Schedler (BMC Research Notes, 2022)
Abstract Objective In children, studies have shown that balance performance is worse in boys compared to girls and further studies revealed inferior performance when arm movement was restricted during balance assessment. However, it remains unclear whether restriction of arm movement during balance testing differentially affects children’s balance performance (i.e., boys more than girls). Thus, we compared the influence of arm movement on balance performance in healthy boys versus girls (mean age: ~ 11.5 years) while performing balance tasks with various difficulty level. Results In nearly all tests, balance performance (i.e., timed one-legged stance, 3-m beam walking backward step number, Lower Quarter Y-Balance test reach distance) was significantly worse during restricted compared to free arm movement but without any differences between sexes or varying levels of task difficulty. These findings indicated that balance performance is negatively affected by restriction of arm movement, but this does not seem to be additionally influenced by children’s sex and the level of task difficulty.